Research on Locomotive Automatic Transport System for Steel Mills - LIU Guangyong; HU Chunhui; LIU Jianshu; TANG Tao; HUANG Sheng (Kongzhi Yu Xinxi Jishu)
As an important means of cargo transport in steel enterprises, railway transport currently encounters challenges, such as complex operational environments, high on-site operational intensity, elevated safety risks, and low levels of automation. To address these issues, this paper proposes a locomotive automatic transport system that integrates various technologies, such as automatic operation, obstacle detection, fusion positioning, and 5G communication. This solution is designed with a focus on the railway transport requirements of automation, intelligence and flexible manpower line, taking into account specific operational scenarios in steel mills and the principles of train control systems in rail transit. Key technical aspects, such as control modes and obstacle perception, are discussed in further detail. In subsequent implementation within a steel mill, the proposed system enabled multiple functions, including intelligent dispatching, intelligent environmental perception, automatic coupling of running locomotives, stopping with a precision of ±20 cm, and detection of obstacles (larger than 0.3 mm × 0.3 mm × 0.3 mm) at distances ranging from 20 m to 150 m ahead with both error and omission rates lower than 3%. This solution also effectively reduced labor intensity and safety risks for operators, and achieving automatic and intelligent railway transport operations within this steel mill.